Międzynarodowa norma serii ISO 14001 na świecie i w Polsce - porównanie wskaźników środowiskowych wybranych przedsiębiorstw łódzkiej specjalnej strefy ekonomicznej - Gust, Anna (Gospodarka w Praktyce i Teorii, 2011)
This study focuses on international standard ISO 14001 series and number of its certifications all over the world and in Poland. Statistics shows that more and more companies are nowadays willing to have their own environmental management system based on the requirements of ISO 14001 standard. The second part of this study focuses on environmental indicators. The main aim was to analyze and compare them in the global and local level. For the research there were chosen three out of twenty three companies, that obtained ISO 14001 and actually operate within the Lodz Special Economic Zone. Analyzed data shows that there is some environmental policy divergence at the global and local level.